2019
DOI: 10.3389/fneur.2019.00171
|View full text |Cite
|
Sign up to set email alerts
|

Early Identification of High-Risk TIA or Minor Stroke Using Artificial Neural Network

Abstract: Background and Purpose: The risk of recurrent stroke following a transient ischemic attack (TIA) or minor stroke is high, despite of a significant reduction in the past decade. In this study, we investigated the feasibility of using artificial neural network (ANN) for risk stratification of TIA or minor stroke patients. Methods: Consecutive patients with acute TIA or minor ischemic stroke presenting at a tertiary hospital during a 2-year period were recruited. We collected de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 29 publications
1
14
0
3
Order By: Relevance
“…We herein exploited some of the benefits of neural networks, such as the requirement of little (or no) formal statistical training, minor user input, the implicit capacity to detect complex nonlinear relationships between dependent and independent variables, and the ability to delineate all possible interactions between predictor variables 35 . The high predictive power of our models is consistent with known application of ANN to assist with the diagnosis of stroke and prediction of its outcome [35][36][37] . More specifically, the present study demonstrated that the application of ANN helped improve the accuracy of predicting sICH within 72 h of intravenous tPA and the risk of death after the intravenous administration of tPA.…”
Section: Discussionsupporting
confidence: 82%
“…We herein exploited some of the benefits of neural networks, such as the requirement of little (or no) formal statistical training, minor user input, the implicit capacity to detect complex nonlinear relationships between dependent and independent variables, and the ability to delineate all possible interactions between predictor variables 35 . The high predictive power of our models is consistent with known application of ANN to assist with the diagnosis of stroke and prediction of its outcome [35][36][37] . More specifically, the present study demonstrated that the application of ANN helped improve the accuracy of predicting sICH within 72 h of intravenous tPA and the risk of death after the intravenous administration of tPA.…”
Section: Discussionsupporting
confidence: 82%
“…Deep neural networks have been studied for ischemic stroke risk assessment with promising results (92). Artificial neural network have been used to differentiate stroke from stroke mimics (93) and to identify patients at high risk for TIA or minor stroke (94). The use of machine learning in prediction modeling is encouraging but require further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Two different teams of scientists have used ML algorithms to predict three-month functional outcomes following ischemic stroke [ 91 , 92 ]. ML has also been utilized to predict 90-day readmission [ 93 ] and one-year recurrence in patients with ischemic stroke [ 94 ]. In patients undergoing endovascular treatment for ischemic stroke, ML algorithms did not improve outcome prediction when compared to logistic regression [ 95 ].…”
Section: Resultsmentioning
confidence: 99%